Recombinant erythropoietin treatment does not alter the blood pressure despite elevated haematological parameters in normotensive Wistar rats - SULTAN, F.; GANAIE, B.A.; MIR, D.M.; DAR, J.A. (Journal of the Hellenic Veterinary Medical Society, 2020)
Use of erythropoietin (EPO) is believed to be associated with adverse cardiovascular events, especially high blood pressure. Also, its illegal use in blood doping is thought to result in detrimental events both in humans and equines. To test this hypothesis, normal Wistar rats were treated with recombinant erythropoietin (rEPO @ 400 i.u/kg s.c) or normal saline one day apart for one week. Heart rate, systolic, diastolic, mean arterial pressure and blood count were determined. Rats were also observed for their behaviour during the study period. rEPO significantly (P<0.001) increased the erythrocyte count (RBC), haemoglobin (Hb), hematocrit (HCT) and platelet count (PLT) in comparison to control animals. Despite such an increase in hematocrit which in turn increases blood viscosity, the systemic blood pressure and heart rate did not differ between the groups. rEPO treatment did not cause any untoward behavioural change in animals. In conclusion, despite the profound effect on haematological parameters (especially hematocrit), rEPO was without any effect on blood pressure and heart rate and the hypothesis of short-term erythropoietin-induced alterations in cardiac parameters was not verified.